Higher fuel and food prices: impacts and responses for Mozambique - Arndt, Channing; Maximiano, Nelson; Thurlow, James T.; Nucifora, Antonio M. D. (Agricultural Economics, 2008)
Rising world prices for fuel and food represent a negative terms-of-trade shock for Mozambique. The impacts of these price rises are analyzed using various approaches. Detailed price data show that the world price increases are being transmitted to domestic prices. Short-run net benefit ratio analysis indicates that urban households and households in the southern region are more vulnerable to food price increases. Rural households, particularly in the North and Center, often benefit from being in a net seller position. Longer-term analysis using a computable general equilibrium (CGE) model of Mozambique indicates that the fuel price shock dominates rising food prices from both macroeconomic and poverty perspectives. Again, negative impacts are larger in urban areas. The importance of agricultural production response in general and export response in particular is highlighted. Policy analysis reveals difficult trade-offs between short-run mitigation and long-run growth. Improved agricultural productivity has powerful positive impacts, but remains difficult to achieve and may not address the immediate impacts of higher prices.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; agriculture / agricultura

Collaboration and competition in a children's health initiative coalition: A network analysis - Valente, Thomas W.; Coronges, Kathryn A.; Stevens, Gregory D.; Cousineau, Michael R. (Evaluation and Program Planning, 2008)
Activating communities to achieve public health change and initiate policy reform usually requires collective action from many entities. This case study analyzes inter-organizational networks among members of a coalition created to expand health insurance coverage to uninsured children in a large metropolitan area. Six networks were measured: collaboration, competition, formal agreements, receive funding from, send funding to, and greater communication. The response rate was 65.8% (50 of the 76 active members). Positive network questions such as “who do you collaborate with” elicited many network choices whereas negative ones such as “who do you compete with” elicited few. The collaboration network had a core–periphery structure and analysis showed that a large network can be reduced to a small set of core organizations one-sixth the size of the whole. Centrality (out- and in-degree) was associated with perceived organizational function and perceived barriers to success. For example, organizations that received many choices as collaboration partners were more likely to perceive the coalition functioned well than those who received few choices. The study suggests that perceptions of organizational performance are associated with position in the network, central members are more likely to perceive the organization performs well than those on the periphery.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; M - methodology / metodologia; access to services / acesso a serviços; collaboration / colaboração; health - maternal and child / saúde - materno-infantil; health / saúde

Mineral Resources Potential in Mozambique - Lehto, Tapio; Gonçalves, Reinaldo (Geological Survey of Finland, 2008)
The metallic mineral, industrial mineral and construction material resources in Mozambique have been mapped as part of the Mineral Resources Management Capacity Building Project, financed by a grant provided by the Nordic Development Fund. A database covering the location and characteristics of more than 600 mineral indications, showings and deposits within the geographical contract area assigned to the GTK Consortium was created. A total of 140 mineral occurrences were selected for field surveys and assessments that were mainly carried out during May-November 2003, 2004 and 2005. All available data in the report archives of the client, the National Directorate of Geology (DNG), was collected and transferred to the mineral occurrence database, which was then updated with information from field surveys and with new data published by exploration and mining companies on the Internet. New mineral resources maps at the scales 1:50 000 (part of contract area), 1:250 000 and 1:1 million were prepared with the corresponding symbols for various commodities plotted. Favourability maps showing zones with high potential for selected commodities were compiled at the 1:250 000 scale. The mineral resources in Mozambique were described in the four map explanation volumes and summarized in the final reports for the projects Geological Mapping LOT 2 and Geological Mapping LOT 3. As a consequence of increased geological knowledge, facilitated by the activities of the GTK Consortium, investments in Mozambique’s mineral potential by leading international and regional mining companies is already increasing. Currently, global mining houses are investing in exploration for energy minerals (hydrocarbons, coal and uranium), for titanium and zirconium in heavy mineral sands, for gold and gemstones, for the agricultural minerals lime and phosphate and for tantalum, fluorite and other industrial minerals.
Keywords: G - Mozambique / Moçambique; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; ⛔ No DOI found